Differences in Advertising Strategies of Service Marketers: A Content Analysis. Issue 2 (2nd April 2016) - , Utkarsh; Maurya, Harshit; Medhavi, Sanjay
ABSTRACT: A stream of research has investigated advertising strategies for services, but to our knowledge no study has explicitly addressed the differences in advertising strategies of service providers in Indian markets. Moreover, there is lack of research in the role of service types—specifically, search, experience, and credence (SEC)—in advertising of services. To address these issues, advertisements of goods, noncredence, and credence services from print magazines were analyzed using content analyses. The study uncovers the differences in use of appeal, service quality cues, and tangibilization strategies in service advertising.